2021
DOI: 10.3390/vaccines9050427
|View full text |Cite
|
Sign up to set email alerts
|

Influenza Vaccination and COVID-19 Mortality in the USA: An Ecological Study

Abstract: The COVID-19 mortality rate is higher in the elderly and in those with pre-existing chronic medical conditions. The elderly also suffer from increased morbidity and mortality from seasonal influenza infections; thus, an annual influenza vaccination is recommended for them. In this study, we explore a possible county-level association between influenza vaccination coverage in people aged 65 years and older and the number of deaths from COVID-19. To this end, we used COVID-19 data up to 14 December 2020 and US p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
29
1
6

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(39 citation statements)
references
References 48 publications
3
29
1
6
Order By: Relevance
“…In addition, influenza vaccinated patients were less likely to require hospitalization (OR = 0.58), mechanical ventilation (OR = 0.45) and had a shorter hospital stay (OR = 0.76). This result leads to the conclusion that the influenza vaccine is assumed to reduce the COVID-19 disease burden [41]. By contrast, in Italy, independently, Belingeri et al and Pedote et al found no evidence of a relationship between the influenza vaccine and either a COVID-19 diagnosis or a positive SARS-CoV-2 serology test in a group of healthcare workers and COVID-19 infected patients, respectively.…”
Section: The Most Significant Findings Of the Studymentioning
confidence: 97%
“…In addition, influenza vaccinated patients were less likely to require hospitalization (OR = 0.58), mechanical ventilation (OR = 0.45) and had a shorter hospital stay (OR = 0.76). This result leads to the conclusion that the influenza vaccine is assumed to reduce the COVID-19 disease burden [41]. By contrast, in Italy, independently, Belingeri et al and Pedote et al found no evidence of a relationship between the influenza vaccine and either a COVID-19 diagnosis or a positive SARS-CoV-2 serology test in a group of healthcare workers and COVID-19 infected patients, respectively.…”
Section: The Most Significant Findings Of the Studymentioning
confidence: 97%
“…Specifically, they should receive vaccines against S. pneumoniae (PCV13 and PPSV23) [122]. Such vaccinations could stimulate an immune response in older adults; although the data are not fully supportive of this hypothesis, pneumococcal vaccinations could reduce the risk and potentially severe infections, including COVID-19 [123][124][125]. Thindwa et al [119] estimated COVID-19 mortality associated with pneumococcal coinfection and reported that PPSV23 in older adults could reduce potentially pneumococcal-attributable COVID-19 morbidity and mortality.…”
Section: Recommendations Of Pneumococcal Vaccine For Reducing the Ris...mentioning
confidence: 99%
“…As by Fragoulis et al [62], the numbers of vaccinated individuals with ARDs have risen in the season of 2020/2021 and reached 83%. It could also be beneficial in the view of decrease of COVID-19 mortality [63].…”
Section: Vaccination and Rheumatic Pathologymentioning
confidence: 99%